Application Of Quizizz-Assisted Gamification Model to Students' Mathematical Communication Skills and Learning Motivation - hamidah; Wijaya kusuma, Jaka; Sari, Putri Puspita (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to improve student's communication skills and motivation in learning game-based mathematics learning, namely with a gamification model included in the quizizz application. The method used is quantitative research with an experimental approach, which compares the class given the gamified learning model and the class given the traditional learning model. The study results found that the gamification learning model included in the quizizz application was more effective than the traditional learning model. Students' mathematical communication skills improved, and their motivation to learn increased because they considered learning like a game they did every day. That way, students will not feel bored while learning. Keywords: Gamification Model; Quizizz, Math Communication Skills, Learning Motivation